Untethering the Nuclear Envelope and Cytoskeleton: Biologically Distinct Dystonias Arising from a Common Cellular Dysfunction - Nadia A. Atai; Scott D. Ryan; Rashmi Kothary; Xandra O. Breakefield; Flávia C. Nery (International Journal of Cell Biology)
Most cases of early onset DYT1 dystonia in humans are caused by a GAG deletion in the TOR1A gene leading to loss of a glutamic acid (ΔE) in the torsinA protein, which underlies a movement disorder associated with neuronal dysfunction without apparent neurodegeneration. Mutation/deletion of the gene (Dst) encoding dystonin in mice results in a dystonic movement disorder termed dystonia musculorum, which resembles aspects of dystonia in humans. While torsinA and dystonin proteins do not share modular domain architecture, they participate in a similar function by modulating a structural link between the nuclear envelope and the cytoskeleton in neuronal cells. We suggest that through a shared interaction with the nuclear envelope protein nesprin-3α, torsinA and the neuronal dystonin-a2 isoform comprise a bridge complex between the outer nuclear membrane and the cytoskeleton, which is critical for some aspects of neuronal development and function. Elucidation of the overlapping roles of torsinA and dystonin-a2 in nuclear/endoplasmic reticulum dynamics should provide insights into the cellular mechanisms underlying the dystonic phenotype.